I23 Pridopidine exerts neuroprotective effects via activation of the sigma-1 receptor. (12th September 2022) - Geva, Michal; Scaramuzzino, Chiara; Lenoir, Sophie; Lahaye, Romane A; Wang, Shao-Ming; Wu, Hsiang-en; Gershoni-Emek, Noga; Saudou, Frédéric; Su, Tsung-Ping; Hayden, Michael R
Abstract : Pridopidine is a selective and potent S1R agonist in clinical development for HD and ALS. The S1R modulates cellular processes commonly impaired in neurodegenerative disorders, including BDNF expression, autophagy and mitochondrial function. Activation of the S1R exerts neuroprotective effects. Pridopidine demonstrates S1R-mediated neuroprotective effects. In HD neurons, pridopidine increases spine density, enhances mitochondrial function, and mitigates ER and oxidative stress. Pridopidine shows a robust neuroprotection in human HD iPSCs and in mouse HD cortical neurons. Pridopidine's effects are exquisitely S1R-mediated, as its genetic deletion or pharmacological inhibition abolishes these effects. In HD, BDNF levels are reduced in brains of HD patients and in HD mice. BDNF overexpression in HD mice rescues motor and cognitive deficits. In corticostriatal networks from CAG140 mice, BDNF trafficking shows reduced velocity, number of motile vesicles and global flow. Pridopidine restores BDNF flux ~2-fold (p<0.01), and improves synaptic function by ~30% (increased glutamate release, p<0.0001). Pridopidine increases phospho-ERK (pro-survival factor) in the post-synaptic striatal compartment ~5-fold (p<0.01). Pridopidine's effect is abolished by the S1R antagonist NE-100.In ALS, G4C2 repeats in the c9orf72 gene are the most common cause of familial ALS. The G4C2 expansion destabilizes the nucleopore complex inhibiting nucleocytoplasmic transport (NCT). Nuclear transport of the Transcription Factor EB (TFEB) is critical for the initiation of autophagy. Neuronal NSC34 cells overexpressing G4C2 repeats show impaired nuclear transport of TFEB (~40%, p<0.05) leading to impaired autophagy (~30% reduction of LC3-II:LC3-I, p<0.01). Pridopidine rescues NCT of TFEB by ~90%, p<0.01), enhances autophagy (50%, p<0.05), leading to enhanced neuroprotection (~12%, p<0.001).